Efficacy and safety of laquinimod versus placebo in relapsing-remitting multiple sclerosis: a systematic review and meta-analysis of randomized controlled trials - Malik Waleed Zeb Khan; Aizaz Ali; Amna Hussain; Safeena Khan; Ammara Tahir; Muhammad Haris Khan; Touba Azeem; Abdul Moeez; Arysha Monis; Aban Masaud Mian; Fazia Khattak; Moosa Ali; et al. (Journal of International Medical Research)
Objective To investigate the safety and efficacy of laquinimod in treating relapsing-remitting multiple sclerosis (RRMS). Methods An extensive electronic search was conducted across PubMed, Embase, Cochrane Database of Systematic Reviews, and ClinicalTrials.gov to identify suitable studies. Risk of bias was assessed using Cochrane’s Risk of Bias tool. Statistical analysis was performed using RevMan 5.4.1. Results The meta-analysis of four randomized controlled trials including 3665 patients found that laquinimod significantly reduced the annualized relapse rate compared with placebo (mean difference = −0.08, 95% confidence interval [CI] = −0.12, −0.04, I 2  = 0%). For disability progression confirmed at 3 months, laquinimod provided a significant advantage over placebo (hazard ratio [HR] = 0.75, 95% CI = 0.59, 0.96, I 2  = 25%), whereas no benefit was achieved at 6 months (HR = 0.69, 95% CI = 0.45, 1.06, I 2  = 66%). Laquinimod was also significantly better than placebo in maintaining a relapse-free status (risk ratio [RR] = 1.14 95% CI = 1.06, 1.22, I 2  = 10%). Laquinimod had a comparable safety profile as placebo (RR = 1.06, 95% CI = 0.81, 1.39, I 2  = 33%). Conclusions These findings support the efficacy of laquinimod in managing RRMS but necessitate careful monitoring during treatment.